2019
DOI: 10.1002/pld3.187
|View full text |Cite
|
Sign up to set email alerts
|

AtIRE1C, an unconventional isoform of the UPR master regulator AtIRE1, is functionally associated with AtIRE1B in Arabidopsis gametogenesis

Abstract: The unfolded protein response (UPR), a highly conserved set of eukaryotic intracellular signaling cascades, controls the homeostasis of the endoplasmic reticulum (ER) in normal physiological growth and situations causing accumulation of potentially toxic levels of misfolded proteins in the ER, a condition known as ER stress. During evolution, eukaryotic lineages have acquired multiple UPR effectors, which have increased the pliability of cytoprotective responses to physiological and environmental stresses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Reporter constructs involving the IRE1c promoter demonstrated that the gene is expressed in the anther and embryo (Mishiba et al, 2019) Moreno et al (2012) [Colour figure can be viewed at wileyonlinelibrary.com] for a long time, because single knockout mutations in IRE1c had no demonstrable phenotype. However, a role of IRE1c came to light when two groups created a triple ire1a/b/c mutant and reported that it was lethal, and when a heterozygous IRE1c mutation was created in conjunction with ire1a/ire1b (ire1a/ire1b/ire1c/+) it was found to be defective in male gametogenesis (Mishiba et al, 2019;Pu et al, 2019).…”
Section: The Weirdness Of Ire1cmentioning
confidence: 99%
See 1 more Smart Citation
“…Reporter constructs involving the IRE1c promoter demonstrated that the gene is expressed in the anther and embryo (Mishiba et al, 2019) Moreno et al (2012) [Colour figure can be viewed at wileyonlinelibrary.com] for a long time, because single knockout mutations in IRE1c had no demonstrable phenotype. However, a role of IRE1c came to light when two groups created a triple ire1a/b/c mutant and reported that it was lethal, and when a heterozygous IRE1c mutation was created in conjunction with ire1a/ire1b (ire1a/ire1b/ire1c/+) it was found to be defective in male gametogenesis (Mishiba et al, 2019;Pu et al, 2019).…”
Section: The Weirdness Of Ire1cmentioning
confidence: 99%
“…Lu and Christopher were the first to report that ire1b‐2 homozygotes could not be recovered upon selfing heterozygotes (Lu & Christopher, 2008). Pu, Ruberti, Angelos, and Brandizzi (2019) argued that ire1b‐4 , which maintains viability as a homozygote is a ‘functional knockdown allele’ and that complete loss‐of‐function alleles of IRE1b are not viable as homozygotes. Nagashima et al (2011) tried but failed to complement an ire1b‐2 mutant with the wild type copy of the IRE1b gene.…”
Section: Are Two Ire1s Better Than One?mentioning
confidence: 99%
“…In animals, plants, and yeast, the most conserved axis of UPR is Inositol-Requiring Enzyme 1 (IRE1), a hybrid kinase equipped with an N-terminal ER lumen sensor domain and a C-terminal endonuclease (RNase) domain ( Chen and Brandizzi, 2013b ; Ruberti and Brandizzi, 2014 ; Ruberti et al, 2015 ; Srivastava et al, 2018 ; Stefano and Brandizzi, 2018 ; Bao et al, 2019 ). The Arabidopsis genome encodes three isoforms of IRE1: AtIRE1a, AtIRE1b, and AtIRE1c ( Koizumi et al, 2001 ; Mishiba et al, 2019 ; Pu et al, 2019 ). Although AtIRE1a and AtIRE1b have partly overlapping functions in UPR ( Moreno et al, 2012 ; Chen and Brandizzi, 2013b ; Afrin et al, 2020a ; Verchot and Pajerowska-Mukhtar, 2021 ), the two isoforms show functional divergence and play distinct roles in response to various forms of stress.…”
Section: Introductionmentioning
confidence: 99%
“…AtIRE1a is preferentially involved in pathogen-induced UPR whereas AtIRE1b shows higher activation when exposed to abiotic and chemical stress treatments, such as the N -glycosylation inhibitor tunicamycin (Tm) ( Moreno et al, 2012 ). AtIRE1c lacks the N-terminal domain and was shown to be primarily involved in reproductive development ( Mishiba et al, 2019 ; Pu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the endonuclease-independent role of IRE1 has been revealed in Arabidopsis. The protein kinase domain of IRE1 is essential for its role in RIDP to regulate plant growth and development, although the phosphorylation substrates of IRE1 have not yet been identified [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%